2020
DOI: 10.1111/jphp.13336
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological postconditioning: a molecular aspect in ischemic injury

Abstract: Objective Ischaemia/reperfusion (I/R) injury is defined as the damage to the tissue which is caused when blood supply returns to tissue after ischaemia. To protect the ischaemic tissue from irreversible injury, various protective agents have been studied but the benefits have not been clinically applicable due to monotargeting, low potency, late delivery or poor tolerability. Key Findings Strategies involving preconditioning or postconditioning can address the issues related to the failure of protective therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…Interestingly, many studies have also shown that pharmacological preconditioning (PreCo) or postconditioning (PoCo) is beneficial to the ischemic organ. Subsequently, the main advantage of pharmacological PoCo over ischemic preconditioning or pharmacological PreCo is its added clinical feasibility or clinically applicable [47]. CI/R injury is often seen in unannounced clinical situations, such as cardiac arrest or ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many studies have also shown that pharmacological preconditioning (PreCo) or postconditioning (PoCo) is beneficial to the ischemic organ. Subsequently, the main advantage of pharmacological PoCo over ischemic preconditioning or pharmacological PreCo is its added clinical feasibility or clinically applicable [47]. CI/R injury is often seen in unannounced clinical situations, such as cardiac arrest or ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…This immune activation is characterized by the release of signaling molecules from the injured tissue, invoking a potent immune reaction aimed at repairing the damage [19]. Furthermore, adhesion molecules on endothelial cells stimulate circulating white blood cells to adhere to activated endothelial cells, leading to microvascular blockade and the infiltration of immune cells into the brain parenchyma [20].…”
Section: Inflammatory Pathogenesis Of Post-stroke Depressionmentioning
confidence: 99%
“…The mechanism of ischemic postconditioning includes activation of the adenosine receptors, α-adrenergic receptors, opioid receptors, and bradykinin, with activation of pathways such as the PKC, TK, and MAP kinase, or the activation mechanism involves an endogenous trigger such as NO and Ca 2+ ions. The administration of drugs whose effect mimics the mechanism of the action of ischemic postconditioning is called pharmacological postconditioning (FAP) [ 138 , 139 ].…”
Section: Pharmacological Postconditioningmentioning
confidence: 99%